1970
DOI: 10.1039/j19700001516
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of soil minerals. Part VI. Salt entrainment by sodalite and cancrinite during their synthesis

Abstract: The imbibition of salts by sodalite and cancrinite during their hydrothermal formation from kaolinite has been studied. Isotherm contours recalling those of Langmuir's isotherm were observed in sodalite for NaCI, NaBr, NaCIO,, NaCIO,, and Na,CO,.These results have been interpreted in terms of a Donnan equilibrium, in which solid-phase activities were calculated on the experimentally justified assumption that each sodalite cage is capable of accommodating a particular number of each kind of guest molecule, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
3

Year Published

1982
1982
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 0 publications
4
24
0
3
Order By: Relevance
“…A e B são espécies capazes de formar tetraedros (Al e Si) e X pode ser uma variedade de ânions mono e divalentes. A estrutura está baseada em uma cadeia octaédrica truncada formada pela união de átomos de Si e Al ligado tridimensionalmente [8,9].…”
Section: Introductionunclassified
“…A e B são espécies capazes de formar tetraedros (Al e Si) e X pode ser uma variedade de ânions mono e divalentes. A estrutura está baseada em uma cadeia octaédrica truncada formada pela união de átomos de Si e Al ligado tridimensionalmente [8,9].…”
Section: Introductionunclassified
“…The area of the pore opening increases 80% so that the structure becomes much more permeable. The T-O-T' angle increases 200 in going from Na 3 0(AlSiO4)304H 2 0 to NasO(AISiO4) 3 and the sodium atom moves to within 0.24 A of the center of the pore opening. 0.24 A is the displacement required for the Na3 3 * cluster identity to be lost and the structure to be transformed into an expanded Na+ lattice.…”
Section: Framework Atom Substitution and Inter/[tracluster Geometrymentioning
confidence: 99%
“…This has been supported by our recent studies of the nonlinear optical response of the four noncentrosymmetric sodalites with the above compositions (25). Second harmonic generation (SHG) measurements performed on the crystalline powders using Nd-Yag 1064 nm radiation showed that substitution of silicon by germanium in Na 3 [](AlSiO 4 )3o4H 2 0 and Na 3 [](GaSiO 4 ) 3 *4H 2 0 increases SHG efficiency by factor of 3 while substitution of aluminum by gallium in Na 3 0(A1SiO 4 ) 3 *4H 2 0 and Na 3 0(A1GeO4) 3 *4H 2 0 increases SHG by only 30%. Evaluation of the P43m point group X(123) nonzero polarizabiity tensor elements using the SHG measurements for this series is in progress.…”
Section: Framework Atom Substitution and Inter/[tracluster Geometrymentioning
confidence: 99%
See 2 more Smart Citations